Health at the writing desk of John Ruskin: a study of handwriting and illness - Thorpe, Deborah E.; Alty, Jane E.; Kempster, Peter A. (My University, 2020)
Though John Ruskin (1819–1900) is remembered principally for his work as a theorist, art critic and historian of visual culture, he wrote exhaustively about his health in his correspondence and diaries. Ruskin was prone to recurring depressive and hypochondriacal feelings in his youth and adulthood. In 1871, at the age of 52 years, he developed an illness with relapsing psychiatric and neurological features. He had a series of attacks of brain disturbance, and a deterioration of his mental faculties affected his writing for years before curtailing his career a decade before he died. Previous writers have suggested he had a psychiatric malady, perhaps schizophrenia or schizoaffective disorder. But the more obvious conclusion from a close medical reading of Ruskin’s descriptions of his illness is he had some sort of ‘organic’ brain illness. This paper aims to give insight into the relationship between Ruskin’s state of well-being and the features of his writing through a palaeographical study of his letters and diary entries. We examine the handwriting for physical traces of Ruskin’s major brain illness, guided by the historical narrative of the illness. We also examine Ruskin’s recording of his experiences for what they reveal about the failure of his health and its impact on his work. Ruskin’s handwriting does not have clear-cut pathological features before around 1885, though suggestions of subtle writing deficits were present as early as 1876. After 1887, Ruskin’s handwriting shows fixed pathological signs—tremor, disturbed letter formation and features that reflect a slow and laborious process of writing. These observations are more than could be explained by normal ageing, and suggest the presence of a neurological deficit affecting writing control. Our findings are consistent with conclusions that we drew from the historical record—that John Ruskin had an organic neurological disorder with cognitive, behavioural, psychiatric and motor effects.
PUBLISHED
Keywords: John Ruskin; Health; Palaeography